Evaluacion de la Gestion comercial de la Empresa de lacteos y refrescos Prasol de la Parroquia San Luis, Canton Riobamba, Provincia de Chimborazo y su incidencia de ventas en el periodo 2016-2017 - Vásquez Cisneros, María José (2019)
The success of a company is possible with effort links in all its areas, and without a doubt commercial area becomes a determining factor in the achievement of business achievement. Thus, the present investigation focuses on the evaluation of the Commercial Management PRASOL dairy, and soft drink, company in San Luis parish - Riobamba town, to determine its volume of sales impact during 2016-2017, since the company has not carried out a review of its objectives facing sales, and customer satisfaction; opting for an administration guided by experience. Hence the need to establish a situational analysis of PRASOL’s commercial management to evaluate it and, therefore, it is business profitability. The development of this research was framed within a quantitative approach with a non- experimental, transversal, and correlational design applied type, and the levels of research were descriptive, explanatory, exploratory and diagnostic For the analysis, the questionnaire of the EFQM adapted model was used for the administrative area, obtaining a score of 602/900, data that determined a lack in the management capacity in the development of improvements in its value chain and suggesting to optimize factors such as leadership, policies, image, the valuation of people’s talent and the added value for clients. Regarding the analysis of total verified sales, they decreased by 18.55%. Consequently, the net return showed a reduction of 0.70%, falling from 4.20% to 3.50% during the 2016- 2017. For the satisfaction of the external client, the questionnaire of the adapted SERVPERF model was used, evidencing that the clients are SATISFIED with the service offered by the company however, in order to achieve the total satisfaction of the clients, an improvement is necessary in the appearance of the facilities, equipment and communication materials, in the execution of the promised service in an integral and painstaking manner and in the offer of personalized attention. In this way, it was possible to conclude that the activities executed as part of the commercial management have had a direct relationship with sales in terms of volume and profitability.